A Study on Demonetization Impact on Public and Private Banks - Rohan, Vishwakarma; Mallesha, C. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
On November 8, 2016, the Government of India demonized the currencies of Rs 500 and Rs 1000, with the aim of combating corruption, counterfeit currency, black currency and terrorist financing. The total value of the demonized currency was Rs 15.4 trillion, or about 86.9% of the total currency in circulation. Especially in November and December 2016, the hard-hit period was experienced due to demonetization. As an impact of demonetization on Indian banks, there has been a positive change in the planned financial statements of commercial banks. A large amount deposited with the banks created and created a surplus. The total number of accounts opened has increased and the amount deposited into these accounts has also increased. A significant impact of demonetization has also been monitored in the use of electronic banking transactions. The study focuses on the impact of demonetization on public and private banks. The role of cash transactions in an informal economy is crucial, so the current study on how the announcement of demonetization has an impact on the practical price of the banking sector. With 86% of the monetary base washed away, economic activity is likely to be negatively affected in the short term. The sample size of the survey is that of the top five private sector banks and five public sector banks listed in the RNS. The study is carried out by comparing the public and private sectors over a period of 12 days before demonetization and 15 days after demonetization. The result of the test shows that private banks outperform the public sector after demonetization.